The Relationship Between Energy, Protein, and Fat Intake in Pregnant Women with Infant Weight and Length - Mahdiah Mahdiah; Eflin Roito Tampubolon (Ridwan Institute, 2023)
The 2018 Basic Health Research (Riskesdas) data highlights the prevalent issue of Chronic Energy Deficiency (KEK) among pregnant women. This prospective cohort study investigates the correlation between energy, protein, and fat intake in pregnant women and their infants' birth weight and length. Utilizing purposive sampling, third-trimester pregnant women were interviewed through questionnaires and food recall tables. Data processing involved editing, entering, and tabulating, with correlation analysis revealing that inadequate energy intake (61%) and protein intake (51.2%) were typical. Fat intake, predominantly sufficient (87.8%), exhibited minimal inadequacy (5%). Although energy intake influenced body weight, it did not impact birth length. Protein intake affected body length but not body weight, while fat intake influenced body weight without affecting birth length. Notably, most infants exhibited average birth weight (95.1%) and regular body length (95.1%).